Repair of Vascular Ring with Resection of Kommerell Diverticulum and Transposition of Aberrant Left Subclavian Artery - Samas, John; Manetta, Frank; Meyer, David B. (International Journal of Angiology, 2013)
A 32-year-old female presented with dysphagia. Radiographic studies revealed external compression of esophagus by a vascular ring. The anatomy was a right-sided aortic arch with aberrant retroesophageal left subclavian artery, emanating from a large Kommerell diverticulum (KD). Traditional repair with ligamentum division and adhesiolysis leaves a large KD still adjacent to the esophagus with the potential for persistent or recurrent symptoms. The objective of this study was the modification of operative technique to minimize the potential for persistent or recurrent symptoms. The operative repair included resection of KD with transposition of the left subclavian artery into the left carotid artery, in addition to the division of the ligamentum arteriosum and mobilization of the esophagus. The patient's dysphagia resolved and postoperative barium studies showed no residual compression. There were no significant perioperative complications. Resection of KD is a potential adjunct to traditional repair of vascular rings and might offer better long-term palliation by minimizing residual vascular compression of the esophagus.
Keywords: aneurysm; ligation; repair; resection; subclavian; transposition; artery